2020
DOI: 10.1177/1071100720963059
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Rapid Development and Deployment of a Telemedicine Program in a Foot and Ankle Orthopedic Practice

Abstract: Background: A lack of access to care is predictably associated with negative outcomes in foot and ankle surgery. Despite recent advances in telecommunication technologies, the field of orthopedics has been slow to adopt these resources in offsetting barriers to care. The COVID-19 pandemic has forced departments to change their clinical approach, lending unprecedented opportunity to better understand how telehealth may bridge this care gap in foot and ankle practices. The purpose of this study was to assess pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 30 publications
2
25
0
Order By: Relevance
“…Telehealth visits following minimally invasive gynecologic procedures appear to be safe and feasible, and are associated with a high level of patient satisfaction. We were able to demonstrate that patients were highly satisfied with their experience, similar to studies conducted in other surgical specialties [ 2 , 3 ]. Furthermore, we did not find that postoperative telehealth visits led to a delay in the diagnosis of postoperative complications or an increased demand for in-person visits.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Telehealth visits following minimally invasive gynecologic procedures appear to be safe and feasible, and are associated with a high level of patient satisfaction. We were able to demonstrate that patients were highly satisfied with their experience, similar to studies conducted in other surgical specialties [ 2 , 3 ]. Furthermore, we did not find that postoperative telehealth visits led to a delay in the diagnosis of postoperative complications or an increased demand for in-person visits.…”
Section: Discussionsupporting
confidence: 75%
“…Due to social distancing regulations, healthcare providers have adopted widespread use of telehealth visits [ 1 ]. Surgical specialties have already demonstrated successful implementation of telehealth visits into the spectrum of their care [ 2 , 3 ]. These data highlight the feasibility and patient satisfaction with virtual visits during a pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Fifty-nine articles met the inclusion criteria and were considered for the analysis. 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 The excluded thirty-four papers were editorials, letters, duplicate entries, and articles with no discussion on telemedicine even in the full text ( Figure 1 ). The monthly contributions trend of the orthopaedic telemedicine-related articles is shown in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
“… 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 Telemedicine can address the general and specialised needs of osteoporotic patients, paediatric deformities, fracture patients, and sports injuries. 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 High patient and doctor satisfaction has been recorded with telemedicine. 26 It is found to be helpful in decision-making and telephone-based follow-up care.…”
Section: Discussionmentioning
confidence: 99%
“…Telemedicine and virtual consultation methods are also used successfully in orthopedics, which is a branch that frequently uses imaging methods in patient treatment 3,11 . In randomized controlled studies conducted within the scope of this branch, it has been shown that these methods can be used safely in selected patients 4,12 . In order to be used in a wider context, the success of this approach should also be demonstrated by economic and patient satisfaction-based studies.…”
Section: Discussionmentioning
confidence: 99%